Strategi Dakwah Mohammad Natsir, Respon Terhadap Kristenisasi Dan Nativisasi, Serta Implementasinya Pada Dewan Dakwah Islamiyah Indonesia (DDII) - Susilawati, Nofa Nur Rahmah; , Dr. Sudarno Shobron, M.Ag; , Dr. M.A. Fattah Santoso, M.Ag (2015)
The evangelism and nativisation are of the apostasy movement and or lack of aqidah which until today remain a da'wah challenge. Muhammad Natsir as one of the leading national and international figure has a role in responding to the movement. He has a da'wah strategy to oversee the Muslim faith. According to them, this research focuses on the study of how the Mohammad Natsir's da'wah strategy in response to both these challenges, as well as its implementation in the Dewan Dakwah Islam Indonesia (DDII) which is a da'wah institution that was pioneered by M. Natsir. This study aims to determine the Muhammad Natsir's da'wah strategy to face the ummah problems, especially evangelism and nativisation. As well as, it's implementation in DDII to response both of the da'wah challenge.This is a qualitative research with a historical approach analysis, using the method of biographical reconstruction. Techniques of data collection using the library research and interviews with DDII competent administrators as a primary source. As for other sources used are books, journals that discussed the history of evangelism and nativisation in Indonesia as well as the role of M. Natsir to response both. The analysis method used in this study is an inductive analysis. The type of this research is explanatory research which is looking for new things of historical facts such as the implementation of M. Natsir's da'wah thought for later analysis defined as a pattern of strategy in responding to the challenge of evangelism and nativisation. Based on the results of this study, concluded that M. Natsir's da'wah strategy in response to evangelism and nativisation is to strengthen the Islamic faith in a way to make people aware their existence as a Muslim and aware their missionary challenge through education, da'wah fardhiyah, structural da'wah,and cultural da'wah. The steps are chosen is to educate every Muslim and to unite ummah in the middle of Indonesian diversity. The implementation of da'wah in DDII until today have the same strategy, but its content is different appropriate with the conditions of the times.